Fifty Years of Supporting Global Health Research at the NIH Fogarty International Center - Kenneth Bridbord; Kristen H. Weymouth; Ann Puderbaugh; Celia Wolfman; Christopher W. Belter; Joel G. Breman; Peter H. Kilmarx (Ubiquity Press, 2019)
For 50 years, the Fogarty International Center (FIC) has built research capacity particularly in low and middle-income countries responding to national and global public health priorities. Established in 1968 in honor of U.S. Congressman John E. Fogarty, FIC is one of 27 Institutes and Centers at the U.S. National Institutes of Health (NIH). Initially created in response to the HIV/AIDS pandemic in the 1980s and emerging infectious diseases in the 1990s, the Center provided training for approximately 6,000 health scientists from more than 100 countries including 1,000 from the U.S. Current programs are catalytic, addressing national and international institutional capacity strengthening in HIV and other infectious diseases, environmental and occupational health, research ethics, brain disorders, trauma and injury and other non-communicable diseases, tobacco, health systems implementation research, and medical education. Since 1988, FIC provided over $1.5 billion in extramural grants leveraging its relatively modest $50 million extramural budget by $20-$30 million annually. FIC-trained scientists and public health leaders led key studies about malaria vaccines and AIDS prevention trials, became directors of national HIV/AIDS programs, and achieved leadership positions such as Minister of Health. Between 2009 and 2015, FIC cited-papers averaged approximately 1.1% of the NIH total, in comparison to the FIC budget, which averaged only 0.22% of the NIH budget. While maintaining strong commitments to respond to global health threats caused by communicable diseases, FIC is training the next generation of global health researchers focusing on chronic diseases, implementation science and epidemic modeling needed to predict and help contain future global pandemics.